Advances in Extracorporeal Membrane Oxygenation - Volume 3 2019
DOI: 10.5772/intechopen.85103
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications and Neuromonitoring on ECMO

Abstract: Extracorporeal membrane oxygenation is challenged by several potential complications. Adverse neurologic events such as intracranial hemorrhages, strokes, seizures, and brain death are among the most detrimental and even catastrophic of ECMO complications. There are several risk factors related to the patients, their underlying conditions and the therapy itself that predispose these patients to neurologic injuries. In this chapter, we review different types of neurological complications, the identification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 67 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…18 Focal cerebral ischemia may be just as detrimental as global cerebral ischemia in terms of VA-ECMO outcomes, disability, and disruption of cerebral autoregulation. 20 rSO 2 asymmetry should be interpreted carefully, as we found that short episodes of rSO 2 asymmetry observed on the time scale of a few hours are not associated with ABI, but when a patient on average exhibits >8% rSO 2 asymmetry over the entire duration of cNIRS monitoring, the odds of ABI are significantly increased compared to those without asymmetry, which likely represents an ongoing ABI. A failure to recognize and address the presence of ABI in a timely manner can result in poor outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…18 Focal cerebral ischemia may be just as detrimental as global cerebral ischemia in terms of VA-ECMO outcomes, disability, and disruption of cerebral autoregulation. 20 rSO 2 asymmetry should be interpreted carefully, as we found that short episodes of rSO 2 asymmetry observed on the time scale of a few hours are not associated with ABI, but when a patient on average exhibits >8% rSO 2 asymmetry over the entire duration of cNIRS monitoring, the odds of ABI are significantly increased compared to those without asymmetry, which likely represents an ongoing ABI. A failure to recognize and address the presence of ABI in a timely manner can result in poor outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…[15][16][17] It seems likely that these are due to a more stable hemodynamic transition than arterial assessment and the low risk of embolization due to the filtering of thrombi by blood returning to the venous system in VV-ECMO. [3,13] Additionally, due to the close anatomical proximity of the various important structures and the narrow vascular diameter in the pediatric population, ultrasound-guided procedures are recommended for invasive intervention (vascular access and regional anesthetic technique) in children for anatomical assessment and accurate needle insertion. [18][19][20] Image-guided ECMO intervention with real-time ultrasound or fluoroscopy has to be suggested in neonatal intensive care unit and pediatric intensive care unit patients to decrease neurologic injury.…”
Section: Discussionmentioning
confidence: 99%
“…As neuralgic complications have a significant impact on the survival and quality of life in ECMO-treated children, early detection of peripheral neural injury and preventive strategies are required. There are several guidelines for neuromonitoring of the central nervous system, including neuroimaging (cranial ultrasound, CT, and MRI), electroencephalography, transcranial Doppler ultrasound, cerebral near-infrared spectroscopy, biomarkers (S100β, GFAP, neuron-specific enolase, and IL-6), somatosensory evoked potentials, and optic nerve sheath diameter [3] . However, peripheral nerve injury has rarely been reported in previous cases, and there are no recommendations for neuromonitoring of the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations